2021
DOI: 10.1155/2021/6693542
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines that Modulate the Differentiation of Th17 Cells in Autoimmune Uveitis

Abstract: Increasing evidence has suggested that T helper 17 (Th17) cells play a central role in the pathogenesis of ocular immune disease. The association between pathogenic Th17 cells and the development of uveitis has been confirmed in experimental and clinical studies. Several cytokines affect the initiation and stabilization of the differentiation of Th17 cells. Therefore, understanding the mechanism of related cytokines in the differentiation of Th17 cells is important for exploring the pathogenesis and the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 194 publications
(230 reference statements)
0
20
0
Order By: Relevance
“…CD4 + Th1 cells, in an IFN-γ-dependent manner, induce the activation of inflammatory M1 macrophages which, through the release of NO and ROS, aggravate acute uveitis [ 22 , 23 ]. CD4 + Th17 cells produce IL-17 and IL-22, which activate N1 neutrophils and innate lymphoid cells, playing important roles in the development and progression of chronic uveitis [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…CD4 + Th1 cells, in an IFN-γ-dependent manner, induce the activation of inflammatory M1 macrophages which, through the release of NO and ROS, aggravate acute uveitis [ 22 , 23 ]. CD4 + Th17 cells produce IL-17 and IL-22, which activate N1 neutrophils and innate lymphoid cells, playing important roles in the development and progression of chronic uveitis [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to IL-10, IL-35 has strong anti-inflammatory activity by inhibiting differentiation of pathogenic Th1 and Th17 as well as promoting development of Bregs and Tregs (209,210). In addition to IL-10 and IL-35, Bregs could secrete TGF-b, thus, suppressing Th1 proliferation while promoting Treg cells differentiation (211). The role of Bregs in pathogenesis of MS was demonstrated in a study, where the reduction of the naïve/memory Bregs was found during a relapse (212).…”
Section: B Cellsmentioning
confidence: 99%
“…The differentiation of T helper 17 (Th17) cells is induced by a combination of transforming growth factor‐β (TGF‐β) and interleukin (IL)‐6. Inflammatory factors (such as IL‐1βand IL‐23) secreted by activated dendritic cells and macrophages residing in the laminae of the intestine can further promote the differentiation of Th17 cells 6,7 . Activated Th17 cells secrete various cytokines, of which IL‐17A plays a major pro‐inflammatory role 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory factors (such as IL-1βand IL-23) secreted by activated dendritic cells and macrophages residing in the laminae of the intestine can further promote the differentiation of Th17 cells. 6,7 Activated Th17 cells secrete various cytokines, of which IL-17A plays a major pro-inflammatory role. 8 Numerous studies have shown a close association between IBD and Th17 cell levels.…”
mentioning
confidence: 99%